2022
DOI: 10.1111/cns.13994
|View full text |Cite
|
Sign up to set email alerts
|

Altered dynamic functional network connectivity in levodopa‐induced dyskinesia of Parkinson's disease

Abstract: BackgroundTraditional measures of static functional connectivity may not completely re ect the dynamic neural activity of levodopa-induced dyskinesia (LID) in Parkinson's disease (PD). This study was aimed to investigate the dynamic changes of large-scale functional network connectivity in the temporal domain in PD patients with and without LID. MethodsUsing dynamic functional network connectivity (dFNC) analysis, we evaluated 41 PD patients with LID (LID group) and 34 PD patients without LID (No-LID group), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 70 publications
2
12
0
Order By: Relevance
“…To investigate the individualized effects of group-average target tACS in patients with PD, our study used electric field simulation and found that the same tACS electrode placement (FC1 and FC2) can stimulate different functional networks across individuals, indicating the necessity of individual targets in noninvasive neuromodulation. This finding is similar to a previous TMS study, which reveals variabilities in individual functional brain network engagement using the same TMS coil placement [34]. In addition, theta frequency was used in this study due to its involvement in high-order cognitive functions [55] and potential efficacy in PD [23].…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…To investigate the individualized effects of group-average target tACS in patients with PD, our study used electric field simulation and found that the same tACS electrode placement (FC1 and FC2) can stimulate different functional networks across individuals, indicating the necessity of individual targets in noninvasive neuromodulation. This finding is similar to a previous TMS study, which reveals variabilities in individual functional brain network engagement using the same TMS coil placement [34]. In addition, theta frequency was used in this study due to its involvement in high-order cognitive functions [55] and potential efficacy in PD [23].…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, this study first investigated whether the same electrode arrangement (FC1 and FC2) activated the same individual brain networks. Similar to a previous TMS study, we set the minimum activation threshold [34]. For each participant, 80% of the maximum simulated electric field was set as the minimum activation threshold and the vertices with an electric field in the range of 80%–100% of the maximum value were defined as activation zones.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations